Opening Minds in Canada: Targeting Change. (January 2014) - Stuart, Heather; Chen, Shu-Ping; Christie, Romie; Dobson, Keith; Kirsh, Bonnie; Knaak, Stephanie; Koller, Michelle; Krupa, Terry; Lauria-Horner, Bianca; Luong, Dorothy; Modgill, Geeta; Patten, Scott B; et al.
Objective: To summarize the ongoing activities of the Opening Minds (OM) Anti-Stigma Initiative of the Mental Health Commission of Canada regarding the 4 groups targeted (youth, health care providers, media, and workplaces), highlight some of the key methodological challenges, and review lessons learned. Method: The approach used by OM is rooted in community development philosophy, with clearly defined target groups, contact-based education as the central organizing element across interventions, and a strong evaluative component so that best practices can be identified, replicated, and disseminated. Contact-based education occurs when people who have experienced a mental illness share their personal story of recovery and hope. Results: Results have been generally positive. Contact-based education has the capacity to reduce prejudicial attitudes and improve social acceptance of people with a mental illness across various target groups and sectors. Variations in program outcomes have contributed to our understanding of active ingredients. Conclusions: Contact-based education has become a cornerstone of the OM approach to stigma reduction. A story of hope and recovery told by someone who has experienced a mental illness is powerful and engaging, and a critical ingredient in the fight against stigma. Building partnerships with existing community programs and promoting systematic evaluation using standardized approaches and instruments have contributed to our understanding of best practices in the field of anti-stigma programming. The next challenge will be to scale these up so that they may have a national impact.